Smart arm robot using visual basic program - Wee, Joo Ann
The aim of this final year project is to design the software using Visual Basic program to control the robot arm, design the electronic circuit and build the Robot Arm. The controlling of the robot arm using wireless radio frequency technology with the distance of 20metre from the controller. The robot is able to move forward, backward, left, right, rotate 350 degree, and the entire arm with gripper can move easily when using wireless controller.